2013
DOI: 10.1177/0959683613512166
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope composition as indicator for climatic changes during the middle and late Holocene in a peat bog from Maramureş Mountains (Romania)

Abstract: The main goal of this study was to use stable carbon isotopic composition of bulk peat sampled in Tăul Mare-Bardău peat bog, Maramureş Mountains, as a tool to provide paleoclimatic information over the middle and late Holocene in this region. A peat core of 3.60 m was sampled for δ13C analysis, and bulk peat samples were analyzed by isotope ratio mass spectrometry (IRMS) method. δ13C values reveal a maximum variation of 4.69‰ along a 3.6-m-long peat core. We examined the vertical variation of δ13C bulk peat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 55 publications
(141 reference statements)
1
28
1
Order By: Relevance
“…The climate is temperate continental, with average annual temperatures of 15 • C and precipitation of 800 mm (Kristó, 1995). Surrounding vegetation is typical of this altitude in the Carpathians (Cristea, 1993), the bog being located at the upper limit of the beech forest, with spruce also found on surrounding slopes. Vegetation on the bog itself is diverse, with common occurrences of Pinus sylvestris, Alnus glutinosa, and Betula pubescens, alongside various Salix species (Pop, 1960;Tanţau et al, 2003).…”
Section: Geographical Settingmentioning
confidence: 99%
“…The climate is temperate continental, with average annual temperatures of 15 • C and precipitation of 800 mm (Kristó, 1995). Surrounding vegetation is typical of this altitude in the Carpathians (Cristea, 1993), the bog being located at the upper limit of the beech forest, with spruce also found on surrounding slopes. Vegetation on the bog itself is diverse, with common occurrences of Pinus sylvestris, Alnus glutinosa, and Betula pubescens, alongside various Salix species (Pop, 1960;Tanţau et al, 2003).…”
Section: Geographical Settingmentioning
confidence: 99%
“…The principal applicability of bulk peat as a comparably easy and less time consuming approach for stable carbon isotope analyses in palaeoenvironmental peat studies was demonstrated by Pancost et al (2003) and Cristea et al (2014). Even if both authors also express the need for caution in interpreting this variable, further justification for such an approach arises from a comparison study between bulk peat and cellulose d13C which demonstrated common patterns between the two datasets (Jędrysek and Skrzypek, 2005).…”
Section: Stable Isotopesmentioning
confidence: 99%
“…The use of carbon isotope composition of organic matter or coal as an indicator of climatic and palaeoenvironmental conditions is well established in the literature (Cristea et al, 2013;Faure et al, 1995;Gröcke and Wortmann, 2008;Rimmer et al, 2006). During the process of photosynthesis and respiration, both modern and ancient plants preferentially absorb 12 C fraction of CO 2 from the atmosphere and become depleted in 13 Cisotopes.…”
Section: -17mentioning
confidence: 99%
“…Compositional variation between formations, if due to climatic and environmental variables (temperature, water availability, pH) can be identified through carbon isotope analysis (Cristea et al, 2013;Rimmer et al, 2006). (2013), even though the coals tested in this study approach anthracite in rank.…”
Section: Palaeoenvironmental Controlsmentioning
confidence: 99%
See 1 more Smart Citation